2016
DOI: 10.1101/075200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ENVIREM: An expanded set of bioclimatic and topographic variables increases flexibility and improves performance of ecological niche modeling

Abstract: 24Species distribution modeling is a valuable tool with many applications across ecology and 25 evolutionary biology. The selection of biologically meaningful environmental variables that 26 determine relative habitat suitability is a crucial aspect of the modeling pipeline. The 19 27 bioclimatic variables from WorldClim are frequently employed, primarily because they are 28 easily accessible and available globally for past, present and future climate scenarios. Yet, the 29 availability of relatively few other… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
115
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 79 publications
0
115
0
Order By: Relevance
“…We also included various climatic factors and their seasonal variation (Hijmans, Cameron, Parra, Jones, & Jarvis, ; Title & Bemmels, ; Supporting information Table ). We obtained a total of 115 predictor variables: 60 climatic, 16 human disturbance, 29 forest and vegetation and 10 topographic variables.…”
Section: Methodsmentioning
confidence: 99%
“…We also included various climatic factors and their seasonal variation (Hijmans, Cameron, Parra, Jones, & Jarvis, ; Title & Bemmels, ; Supporting information Table ). We obtained a total of 115 predictor variables: 60 climatic, 16 human disturbance, 29 forest and vegetation and 10 topographic variables.…”
Section: Methodsmentioning
confidence: 99%
“…Both the NLCD and Cropland datasets were categorical rasters at 30‐m resolution. A topographical roughness index, a topographical wetness index and a continentality raster (30 arc‐seconds continuous rasters) from the ENVIREM dataset (Title & Bemmels, ) were adopted to model topographical heterogeneity across the study domain. Indices for topographical roughness and wetness were intended to help differentiate wetlands and surface waters from other landscape components while continentality (average coldest month temperature subtracted from average warmest month temperature in °C) aided in distinguishing between terrestrial and marine climate regimes (Sayre, Comer, Warner, & Cress, ).…”
Section: Methodsmentioning
confidence: 99%
“…Using 100 random repetitions, we excluded the points that were separated by a distance of <10 km, keeping as many records as possible. This distance was selected to reduce the associated geographic bias, as a function of the heterogeneity of the study area and the performance values reported in the literature (Anderson & Raza, ; Boria et al., ; Galante et al., ; Title & Bemmels, ). After filtering, we obtained 48 presence records that we used to construct the model.…”
Section: Methodsmentioning
confidence: 99%
“…Given that there is evidence that the impact of human activities contributes to the prevalence and distribution of the pathogen (Adams et al., ; James et al., ; O'Hanlon et al., ), we included a layer corresponding to the ecological footprint of human activities (Sanderson et al., ). The ENVIREM set of climate variables was also included, as they notably improve the performance of the models (Title & Bemmels, ). These layers correspond to potential evapotranspiration (PET), which is a measure of the loss of water from the land's surface via evaporation and plant transpiration for a certain area over a specific period of time.…”
Section: Methodsmentioning
confidence: 99%